Assessing the Suitability of Sodium Silicate Activated Granite Dust in the Manufacture of Unfired Clay Bricks - Jotham Mwesige (Uganda Christian University, 2025)
This document contains a comprehensive account of the research conducted in the field of structural engineering in the section of masonry. Research was conducted to assess the suitability of sodium silicate-activated granite dust in the manufacture of unfired clay bricks in the quest for solutions to failure for brick making in Budondo sub-county, Jinja district, Eastern Uganda. The study was conducted to provide a masonry unit in to proximity of the local population who incur higher expenses over buying bricks from a distant area. Unfired bricks have gained favor by the Sustainable Development Goals, conventions, and protocols, where there is a need to reduce the carbon footprint and environmental protection. Sodium silicate-activated granite dust is a geopolymer that both chemically and physically modifies clay soils to become suitable for brick making. Clay soils used have a grading modulus of 0.05, PI of 16.8%, Sg of 2.61, and lower chemical suitability for brick making of 25.85%. Granite dust used had a grading modulus of 1.368, Sg of 2.72, and chemical suitability of 94.78%. Sodium, silicate activator had a modulus of 1.29 with 56.4% silica, and 43.6% sodium, making it suitable for activating granite dust (Provis & Van Deventer, 2009) On blending local clay with activated granite dust the improvement of grading modulus of 1.905, chemical suitability was 96.11% PI was 10.6%. It was found that unfired bricks made from sodium silicate activated granite dust had a compressive strength of 4.9MPa and load bearing capacity of 138.96KN accrued to good bearing capacity for low-cost buildings and self-weight walls. The brick had a water absorption capacity of 13.75% and efflorescence value which showed nil results. The brick is therefore good for masonry wall construction. The content in this document is organized in five chapters with chapter one having the introduction part of the study, chapter two contains the literature review and chapter three contains the methodology which explains how to obtain the objectives of the study. Chapter four is detailed with results and discussions of the study, and the final chapter, which is chapter five, contains the conclusions and recommendations.
Undergraduate